2004
DOI: 10.1590/s1516-89132004000100012
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen balance of starting barrow pigs fed on increasing lysine levels

Abstract: The effects of increasing lysine levels on nitrogen balance of pigs fed on low protein diets were evaluated. Four treatments (diets) containing lysine levels (0.8, 1.0 1.2 and 1.4%) were applied to 12 starting (20.0 ± 1.8 kg) barrow pigs. Methionine, threonine and tryptophan were kept constant to the lysine ratio in all diets. Feces and urine were collected during a 5-day period. Nitrogen output in urine (NOU), total nitrogen output (TNO), nitrogen retention (NR), net protein utilization (NPU), biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
10
1
1
Order By: Relevance
“…This result differs from those found by Moreira et al (2004) who observed a quadratic effect for the variable / AN. However, this relationship may have been affected by the addition of other non-essential amino acids in the diet, for example, tryptophan (Oliveira, 2004;Zangeronimo et al, 2007).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This result differs from those found by Moreira et al (2004) who observed a quadratic effect for the variable / AN. However, this relationship may have been affected by the addition of other non-essential amino acids in the diet, for example, tryptophan (Oliveira, 2004;Zangeronimo et al, 2007).…”
Section: Resultscontrasting
confidence: 99%
“…Moreover, the variation in levels of lysine ratio of 0.7 to 1.3%, the level in 3400 kcal / kg, provided a difference in the retention of N 13.44%, indicating the importance of manipulating the levels this amino acid in the diet. Moreira et al (2004) observed a quadratic effect for nitrogen retention by working with diets with 3400 kcal / kg digestible energy and 14% crude protein supplemented with lysine (0.8, 1.0, 1.2 and 1.4%) for barrows from 20 kg. Similar data for reduced levels of CP are reported by Oliveira (2004).…”
Section: Resultsmentioning
confidence: 97%
“…Nitrogen digestibility as well as balanced or retained nitrogen (NR) were determined by measuring nitrogen intake (dry matter (DM) basis) and nitrogen excretion. Nitrogen absorption (NAB), BVFP and NPU were calculated according to [9]. The coefficient of total tract apparent (CTTAD) and CAM were calculated using equations as shown in [10].…”
Section: Methodsmentioning
confidence: 99%
“…Ferric oxide (Fe 2 O 3 ) was added (2.0 %) to mark the beginning and the end of collection period. Total feces and urine were collected daily, in plastic bags and stored in a freezer until laboratory analyses (Moreira et al, 2004). The digestibility coefficients of dry matter (DCDM), crude protein (DCCP), gross energy (DCGE) and the coefficient of metabolization of gross energy (CMGE) of SH were calculated, considering total collection method (Fialho et al, 1979 andMoreira et al, 1994).…”
Section: Experiments I (Digestibility Trial)mentioning
confidence: 99%